Tratamento do linfedema de membro superior após a cirurgia de câncer de mama por meio do fortalecimento muscular associado à terapia física complexa - Luz, Roberta Pitta Costa [UNIFESP] (2016)
Objective: Compare the complex physical therapy alone or with the combination of muscle strength training in patients with lymphedema after treatment for breast cancer. Methods: Prospective randomized study trial selected patients from April 2014 to December 2015. The complex physical therapy (CPT) group performed CPT and the strengthening group (ST) held CPT associated with muscle strengthening. The study enrolled 42 patients, six included by intention to treat, with CPT group (n=22) the ST group (n= 20).Patients in group strengthening performed 2 sets of 10 repetitions exercises at 40% of maximum resistance during the first week, increasing to 3 sets with 10 repetitions during the second week and on the third week 3 sets with 15 repetitions. The treatment was carried out for eight weeks, 50 minutes per session, twice per week. From sixteen sessions, patients could have no more than four absences, totaling at least twelve sessions at the end of the study. Results: Both groups showed similar improvement, increasing the range of motion in: shoulder flexion, extension, adduction, abduction and external rotation. The same did not happen with internal rotation, which showed less improvement in ST group compared to the CPT (p=0,034). For shoulder strength variables, both groups showed the same pattern of improvement. Regarding upper limb volumetry, the ST group had a greater volume when compared to CPT group (p=0,006), both before and after treatment. However, the effect of variance between time and group was not significant (p=0.797). On ST group there was a reduction on lymphedema volume comparing before (1ª session) and after (16ª session) treatment (p<0.001). Conclusion: There was no difference between CPT associated with strengthening exercises and performed alone. However, strengthening exercises can be performed by patients with lymphedema without increasing the risk of upper limb volume.